2019
DOI: 10.1155/2019/2829798
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L3 Inhibition Induces Cell Cycle Arrest at the G0/G1 Phase in Colorectal Cancer Cells through Downregulating CCND1 and pRb1-ser807/811

Abstract: The molecular mechanism for colorectal cancer to develop remains unelucidated. To find biomarkers related to colorectal cancer development, we analyzed the gene expression profile of 380 colorectal cancer patients and 51 healthy controls by R software. Finally, 1579 upregulated differential expression genes (DEGs) and 3218 downregulated DEGs were identified. Then, the top 20 upregulated DEGs were compared with 181 upregulated DEGs that we reported previously, and 11 overlapped DEGs were found. NFE2L3 (nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Several studies have reported that decreased NFE2L3 expression inhibits proliferation of cells 15 , 18 . To investigate the potential effect of NFE2L3 on HepG2 cell proliferation, NFE2L3 shRNA interference lentiviral vector was performed to knockdown NFE2L3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that decreased NFE2L3 expression inhibits proliferation of cells 15 , 18 . To investigate the potential effect of NFE2L3 on HepG2 cell proliferation, NFE2L3 shRNA interference lentiviral vector was performed to knockdown NFE2L3.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the above results, the expression of CDK2 and PCNA also decreased, it is further confirmed that NFE2L3 plays an important role in cell growth and proliferation. Cyclin D1 is a key mediator of cell growth and proliferation, some researches had proved that NFE2L3 regulated the expression of cyclin D1 in CRC while another article pointed out that the silencing of NFE2L3 will increase the level of DUX4, a direct inhibitor of CDK1, and reduce the proliferation and tumorigenicity of colon cancer cells 15 , 18 . In addition, both cytoplasmic and nuclear β-catenin were decreased by knockdown NFE2L3, indicating NFE2L3 significantly regulated transcription of β-catenin in liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8A). We, in addition, tested the expression of CCND1 whose down-regulation is associated with G 0 /G 1 arrest [28] but missed from the dataset we used for SRFG identi cation. CCND1 was down-regulated to approximately 20% and 60% of the control in SNPRD1-silenced MCF7 and MDAMB231 cells at both gene and protein expression levels (p = 0.022 at the gene expression level, p = 1.53E-4 at the protein expression level in MCF7, p = 0.0023 at the gene expression level, p = 1.7E-166 at the protein expression level in MDAMB231, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Downward-regulated expression of CDCA5 [29,30], NDC80 [31], CCNA2 [32] on SNRPD1 silencing suggested reduced synthesis of DNA and proteins as well as recessed cell mitosis. Further evidence on reduced CCND1 expression after knocking down SNRPD1 implicated the accumulation of cells in the G 0 /G 1 state given the regulatory role of CCND1 in triggering G /G 1 cell cycle arrest [28].…”
Section: Discussionmentioning
confidence: 98%